(3GdPNjQI GdNhGQRejIs - (3ESeGYjd Hf MSjf GdMSjfj, CHh EHQGgje, Rjf GdOjf GdLQLGfj,J (B531 (3g` s
(3ChdgG (B:s
(3EYdehG CNhGfi CjOce Gddg hZjGi HQMeJg Efi HYO HdhZi GdSHYjf ef YeQi LeYJ HNhGQRe cJGH GdPNjQI GdNhGQReTGgjI ai GdWH s
(3BNQgG (B:s
(3BNQ GdehLhO efg GdHGH GdQGHY ai eYQaI SHH GdehJ aLCI SHH GdehJ aLCI gh EeG GfadGJ GdQhM ef GdbdH HZJI adPdc jfHZi Gf jfbHV NUH GdHOf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B824s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs